Molecular characterization of the tet (M)-carrying transposon Tn7124 and plasmids in Escherichia coli isolates recovered from swine - Yingying Liu; Yingying Liu; Zhu Qiao; Yan Ma; Mingcheng Wang; Gongzheng Hu; Enzhong Li (Frontiers in Veterinary Science)
Here, we report the genetic features and evolutionary mechanisms of two tet (M)-bearing plasmids (pTA2 and pTA7) recovered from swine Escherichia coli isolates. The genetic profiles of pTA2 and pTA7 and corresponding transconjugants were accessed by S1 nuclease pulsed-field gel electrophoresis and Southern hybridization, followed by whole genome sequencing and bioinformatics analysis. The biological influences of pTA2 and pTA7 were determined by stability and direct competition assays. Both pTA7 and pTA2 had the IncR backbone sequences but differed in the multidrug resistance region (MDR). The MDR of pTA2 consisted of sul3, tet (M), qnrS1, bleO, oqxAB, floR, aadA1, cmlA1, aadA2, and tet (A)-tetR (A) in addition to 22 insertion sequences. Notably, pTA2 carried the novel complex Tn7124 (IS26-ctp-lp-tet (M)-hp-IS406tnp-IntI4-IS26) harboring tet (M). The fragment carrying tet (M) (IS26-ctp-lp-tet (M)-IS406 tnp-ctp-aadA1-cmlA1-aadA2-dfrA12-IntI1), named Tn6942-like, and the two resistance modules ISVsa3-VirD2-floR-lysR and tet (A)-tetR (A) were located in the MDR of pTA7. Both pTA2 and pTA7 were highly stable in E. coli DH5α cells with no fitness cost to the host or disadvantage in growth competition. These results indicate that transposons carrying tet (M) continuously integrate via mediation with an insertion sequence, which accelerates the transmission of tet (M) in E. coli isolates through integration of other drug-resistant genes, thereby posing a potential serious threat to the efficacy of clinical treatment.